The utilization of unified protocols in behavioral cognitive therapy in transdiagnostic group subjects: A clinical trial - de Ornelas Maia, Ana Claudia Corrêa; Nardi, Antonio Egidio; Cardoso, Adriana (Journal of affective disorders, 2015)
The practicing of protocols based on behavioral cognitive therapy (CBT) have been frequently used in the last decades and adapted to better manage the necessities of patients and providers. The goal is to build a treatment that is evidence-based – for that reason the unified protocol for multiple emotional disorders (transdiagnostics) have been utilized to simplify treatment – without losing scientific traits. The main goal of this study is to evaluate the unified protocol in groups of patients with depression and anxiety disorders. In a pool of 48 subjects, divided in two groups, one was submitted to 12 intervention sessions of the unified protocol while the other was solely given medication. MINI, BAI and BDI were the instruments used at the beginning and at the end of treatment. The results were highly significant (p<0.001) in as much as with the improvement of anxiety and depressive disorders as it was in the group which was treated with the unified protocol compared with the group which was only given medication Limitations of this study were the number of sample participants and the non-randomization of subjects in both groups. Group therapy has not been largely implemented though it is deemed very useful for treatments when the unified protocol is used in transdiagnostic patients. Not only does it allow for emotional stabilizing and socialization but it also enables subjects with an altruistic feeling amongst themselves.